Correction: Identification of Novel Pre-Erythrocytic Malaria Antigen Candidates for Combination Vaccines with Circumsporozoite Protein. - C Speake; A Pichugin; T Sahu; V Malkov; R Morrison; Y Pei; L Juompan; N Milman; S Zarling; C Anderson; N J MacDonald; S Wong-Madden; et al. (PLoS ONE, 2016)
[This corrects the article DOI: 10.1371/journal.pone.0159449.].